Analysis of Business Feasibility Studies in MSMEs Tahu and Tempe Business Success Jaya Mahato Village Tambusai North - Novianisa, Ariela; Syafitri, Kiki; Rahmat, Shah; M. Reynaldi Putra , Efendi (Basecamp Economics PubMed, 2023)
To evaluate the feasibility of a business venture, both financial and non-financial factors are taken into consideration. The assessment of feasibility involves analyzing non-financial elements, with a specific focus on production and marketing aspects. The financial aspects of Tofu and Tempeh Sukses Jaya's commercial production were analyzed using metrics such as payback period (PP), net present value (NPV), internal rate of return (IRR), and profitability index (PI) to determine its overall feasibility. Based on the analysis, it was concluded that the business is feasible due to its advantageous location and convenient accessibility. The Tofu and Tempeh Sukses Jaya business appears to be viable due to its strategic and easily accessible location, modern technology, and straightforward production process. Feasibility is ensured by high product quality, imported raw materials, competitive pricing, extensive distribution channels, and effective promotional efforts by the owner to ensure consumer awareness. The financial analysis suggests that the Tempeh Tofu business could be viable over a 10-year project duration with a 10 percent discount rate. According to the evaluation criteria, the business has a 6-month payback period (PP), a net present value (NPV) of IDR 161,565,200, a profitability index (PI) of 1.6%, and an internal rate of return (IRR) of 30%, all of which indicates the business's financial feasibility.